Single‐Column Modeling of Convection During the CINDY2011/DYNAMO Field Campaign With the CNRM Climate Model Version 6. (2nd March 2018) - Abdel‐Lathif, Ahmat Younous; Roehrig, Romain; Beau, Isabelle; Douville, Hervé
Abstract: A single‐column model (SCM) approach is used to assess the CNRM climate model (CNRM‐CM) version 6 ability to represent the properties of the apparent heat source ( Q 1 ) and moisture sink ( Q 2 ) as observed during the 3 month CINDY2011/DYNAMO field campaign, over its Northern Sounding Array (NSA). The performance of the CNRM SCM is evaluated in a constrained configuration in which the latent and sensible heat surface fluxes are prescribed, as, when forced by observed sea surface temperature, the model is strongly limited by the underestimate of the surface fluxes, most probably related to the SCM forcing itself. The model exhibits a significant cold bias in the upper troposphere, near 200 hPa, and strong wet biases close to the surface and above 700 hPa. The analysis of the Q 1 and Q 2 profile distributions emphasizes the properties of the convective parameterization of the CNRM‐CM physics. The distribution of the Q 2 profile is particularly challenging. The model strongly underestimates the frequency of occurrence of the deep moistening profiles, which likely involve misrepresentation of the shallow and congestus convection. Finally, a statistical approach is used to objectively define atmospheric regimes and construct a typical convection life cycle. A composite analysis shows that the CNRM SCM captures the general transition from bottom‐heavy to mid‐heavy to top‐heavy convective heating. Some model errors are shown to be related to the stratiform regimes. The moistening observed during the shallow and congestus convection regimes also requires further improvements of this CNRM‐CM physics. Key Points: A single‐column version of the CNRM climate model is evaluated in the context of the CINDY2011/DYNAMO field campaign A statistical analysis approach is used to define convective regimes and assess the model ability to reproduce their properties Model biases are specifically related to the representation of shallow convection and the stratiform component of convection